2009
DOI: 10.1017/s1463423609990405
|View full text |Cite
|
Sign up to set email alerts
|

Public involvement in health research: a case study of one NHS project over 5 years

Abstract: Background: Public involvement, both in the National Health Service (NHS) and in clinical research, is promoted as an important democratic principle. The declared aims are to reduce professional autocracy and allow a broader ownership of the research agenda; also to improve the design of, and recruitment and retention of patients to, clinical studies. There have been a number of national initiatives in the UK to improve public input to clinical research activities, but very few reports of effective and sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(65 citation statements)
references
References 11 publications
0
65
0
Order By: Relevance
“…147,159 Commitment to the principles of user involvement All interviewees expressed strong support for the principles of user involvement. Researchers interviewed early on in the evaluation discussed the positive, practical impacts that they expected DUAG members could have on the research, such as ensuring that research participants are not overburdened and improving the wording of participant information material.…”
Section: Discussionmentioning
confidence: 99%
“…147,159 Commitment to the principles of user involvement All interviewees expressed strong support for the principles of user involvement. Researchers interviewed early on in the evaluation discussed the positive, practical impacts that they expected DUAG members could have on the research, such as ensuring that research participants are not overburdened and improving the wording of participant information material.…”
Section: Discussionmentioning
confidence: 99%
“…79,[85][86][87] Moreover, qualitative data collection by service users as co-researchers has been claimed to improve validity and provide better-quality data. [88][89][90] Dissemination of research findings is also reported as gaining from PPI networks to increase access to peers 81 and relevant sections of the community, 15 and making information more broadly readable. 31,72 There are fewer published claims for PPI as playing a significant role in implementing findings, but, in a US public health research programme, Krieger et al 86 report PPI-related implementation of changes by increasing their cultural relevance.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
“…These include increased relevance of the research through identifying research questions and prioritising research agendas, appropriate research conduct, addressing ethical tensions and matching research with policy objectives. 12,[15][16][17][18][19] These three drivers have resulted in PPI being imperative for health research in the UK. However, despite this, PPI is poorly defined and conceptualised, 20,21 with varied definitions and terms used to describe it.…”
Section: Stage 3: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 This is in contrast to the findings from a large number of observational evaluations where involvement has been reported to have a major impact at this stage of the research. 4,[30][31][32][33][34][35] Patient-generated information has been reported to be more accessible and acceptable to other patients, which is then understood to lead to better recruitment and retention. The discrepancy between the findings from the observational evaluations and those from this experimental evaluation can be explained by considering the contextual factors that appear to influence whether this type of involvement is likely to make a difference (Box 4).…”
Section: The Evidence From Experimental Evaluationmentioning
confidence: 99%